Особенности развития ипотечного кредитования в Республике Карелия (Путеводитель предпринимателя)
The mortgage lending market in the Republic of Karelia for the period 2006-2011 is analyzed in the article. The analysis of change of the total amount of credits, the average interest rates on a mortgage, the credit period on mortgage loans is carried out. The mechanisms for support of the mortgage market from part of the government are considered. The Strategy for development of the mortgage lending in the Russian Federation until 2030 was estimated by author.